Static Output Feedback Control With Damping Curve Adaptation for Semi-Active Suspension With Magneto-Rheological Damper - Donghyun Kim; Jinwoo Kim; Soonpyo Yoon; Yonghwan Jeong (IEEE Access)
This paper presents an integrated control algorithm of a linear quadratic static output feedback (LQSOF) controller and a nominal damping controller for an MR damper-based semi-active suspension system. It is difficult to achieve feedback control for suspension with a full-car model due to difficulties involved in estimating vehicle states and responding to high-frequency disturbances. To overcome these challenges in feedback controller implementation, the LQSOF controller is used to provide feedback on estimable states and to improve ride comfort for low-frequency disturbances. For high-frequency disturbances, the nominal damping curve of the MR damper is adjusted to reduce body vibration. The required signals are acquired using a suspension state estimator based on accelerometers that are placed on the vehicle body and wheels. The estimator is composed of a bandwidth filter and a vehicle geometry model to be implemented on a low-cost embedded ECU. The proposed algorithm was evaluated via vehicle tests with passive suspension and the originally equipped electronic control suspension system. Vehicle test results showed that, compared to the base algorithms, the proposed algorithm achieved improved ride comfort and road adhesion in various driving scenarios.